Implementation of Community Corrections in Oregon, Colorado, and Connecticut (1981) - Palumbo, Dennis J. ([Verlag nicht ermittelbar], 1985)
Data were collected from three states to evaluate the success of community corrections programs and to identify the conditions that underlie these successes. In-person field interviews, telephone interviews, and mailback questionnaires were used at state, county, and district levels. The variables in the study were designed to examine the kinds of people who implement and maintain these programs, the level of commitment by judicial and prison officials to these programs, community support, and the goals of cost reduction, work training, and rehabilitation.